Schooling, Family Background and Adoption: Is it Nature or is it Nurture? - Erik Plug; Wim P. M. Vijverberg (Institute for the Study of Labor (IZA), 2001)
When parents are more educated, their children tend to receive more schooling as well. Does this occur because parental ability is passed on genetically or because more educated parents provide a better environment for children to flourish? Using an intergenerational sample of families, we estimate on the basis of a comparison of biological and adopted children that at most 65 percent of the parental ability is genetically transmitted.
Keywords: J24; J13; I21; 330; Intergenerational mobility; human capital; genetic transfers; adoption; Bildungsverhalten; Bildungsniveau; Familiensoziologie; Schätzung; USA